Usefulness of Cardiac Computed Tomography in Spontaneous Coronary Artery Dissection - Turcotte-Gosselin, Frédéric (CJC Open, 2020)
Spontaneous coronary artery dissection (SCAD) is a cause of myocardial infarction with nonobstructive coronary arteries. We describe a case of SCAD in a 39-year-old postpartum woman who presented with acute anterior myocardial infarction, no coronary occlusion but a suspicious coronary angiography. A coronary computed tomography angiogram demonstrated a left anterior descending intramural hematoma confirming the diagnosis. Teaching points emerging from this case are that SCAD and other causes of myocardial infarction with nonobstructive coronary arteries should be investigated, especially because the outcome is not benign. Also, coronary computed tomography angiogram should be considered as a part of the workup and follow-up for SCAD.